Comparison of Upper Lip Bite Test with Modified Mallampati Test and Thyromental Distance for Prediction of Difficult Intubation - Koirala, Sabin; Shakya, Bigen Man; Marhatta, Moda Nath (Nepal Journal of Medical Sciences, 2020)
Introduction: The prediction of difficult intubation using simple bedside test is of great importance to prevent mismanagement of airway. This study was conducted to compare Upper Lip Bite Test (ULBT) with Modified Mallampati Test (MMT) and Thyromental Distance (TMD) for the prediction of difficult intubation. Method: This was descriptive cross-sectional study conducted in 121 patients of American Society of Anaesthesiologists Physical Status (ASA PS) I and II patients scheduled for elective surgery requiring general anaesthesia with endotracheal tube. The airway assessment of the patients was done one day prior to the surgery using Upper Lip Bite Test (ULBT), Modified Mallampati Test (MMT) and measurement of Thyromental Distance (TMD) . On the day of surgery during laryngoscopy, Cormack-Lehane (CL) grading was recorded. The CL grading of III and IV was labeled as difficult intubation. The Sensitivity, Specificity, Positive Predictive Value (PPV), Negative Predictive Value (NPV), Likelihood Ratio (LR) of ULBT, MMT and TMD were calculated and compared. Results: The total percentage of difficult intubation, defined by Cormack-Lehane (CL) III and IV was 16.52 %. The sensitivity, specificity, PPV, NPV and accuracy of Upper Lip Bite Test (ULBT) was 50%, 100%, 100%, 91% and 91.74% respectively. ULBT had a significantly higher sensitivity, specificity and PPV when compared to MMT or TMD or MMT and TMD when combined together. Conclusions: Upper Lip Bite Test (ULBT) is better predictor of difficult intubation and it should be used along with other test during airway assessment.